2017
DOI: 10.1080/07448481.2017.1341897
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion identification and sexual assault risk detection among college student sexual assault victims and nonvictims

Abstract: Findings suggest that differences in social information processing, specifically recognition of others' emotions, are associated with sexual assault risk detection. College prevention programs could incorporate emotional awareness strategies, particularly for men and women who are sexual assault survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The abbreviated emotion recognition task for the present study was drawn from a peer‐reviewed emotion recognition task we developed and tested in a pilot study sample (Melkonian et al, 2017). Pilot testing was conducted among 234 college students (64.7% female, 45.1% first‐year students, and 86.8% Caucasian) who completed the task through an online survey administration software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abbreviated emotion recognition task for the present study was drawn from a peer‐reviewed emotion recognition task we developed and tested in a pilot study sample (Melkonian et al, 2017). Pilot testing was conducted among 234 college students (64.7% female, 45.1% first‐year students, and 86.8% Caucasian) who completed the task through an online survey administration software.…”
Section: Methodsmentioning
confidence: 99%
“…Additional behavioral implications of these findings should also be examined. Given that impaired emotion recognition has been associated with increased aggression and behavioral problems (e.g., Penton‐Voak et al, 2013) and impaired processing of other social cues such as risk cues for sexual assault (e.g., ​Melkonian et al, 2017), future studies should examine the behavioral implications of impaired emotion recognition as a result of alcohol intoxication. Interventions that aim to reduce alcohol use through education about the effects of alcohol may consider incorporating information regarding the social information processing impairments resulting from intoxication and may incorporate social emotion processing training.…”
Section: Implications and Recommendations For Further Researchmentioning
confidence: 99%
“…Nowadays, the booming DL technology has gradually been applied to study the behavior, state, and fatigue of students in classrooms (Stoeve et al, 2021). For example, Melkonian et al (2017) and Song et al (2021) found that the concentration degree of students in the classroom could be evaluated by profile face detection algorithms, changes in eye closure, and head-up and head-down behavior recognition. Hu and Zhang (2021) proposed an eye and nose detection method using a facial recognition model based on DL to evaluate the attention of the students in the classroom.…”
Section: Teaching Techniques Of Ideological and Political Courses In Colleges And Universitiesmentioning
confidence: 99%
“…Sexual assault victimization is associated with a host of negative mental health outcomes including depression, anxiety, traumatic stress, and substance use disorders (Acierno et al, 2002; Burnam et al, 1988; Chivers-Wilson, 2006; Frank & Anderson, 1987; McFarlane et al, 2005; Ullman & Brecklin, 2002), and an increased risk of revictimization. The increased risks of revictimization may be a function of impaired ability to detect risk (Melkonian et al, 2017; Soler-Baillo et al, 2005).…”
mentioning
confidence: 99%